2012
DOI: 10.1002/art.33426
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin22–52 combats inflammation and prevents systemic bone loss in murine collagen‐induced arthritis

Abstract: Conclusion. Our findings indicate that adrenomedullin 22-52 , which has no vasoactive or tumorinducing effects, is a potent antiinflammatory and boneprotective agent in this arthritis model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Other publications seem to support our findings when properly interpreted. For instance a study used the peptide fragment AM 22−52 , trying to take advantage of its immunomodulatory action, and found that it prevented bone loss in a model of collagen-induced arthritis (Ah Kioon et al, 2012 ). As explained above, this fragment is an AM inhibitor and, as such, it has similar effects to our small molecule inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Other publications seem to support our findings when properly interpreted. For instance a study used the peptide fragment AM 22−52 , trying to take advantage of its immunomodulatory action, and found that it prevented bone loss in a model of collagen-induced arthritis (Ah Kioon et al, 2012 ). As explained above, this fragment is an AM inhibitor and, as such, it has similar effects to our small molecule inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Target sites comprise the cardiorespiratory organs and immune cells . Adrenomedullin has been shown to be anti‐inflammatory in animal models of sepsis, pancreatitis, arthritis and colonic inflammation . Adrenomedullin was also reported to inhibit cell proliferation and inflammatory mediator secretion by synovial fibroblasts of rheumatoid arthritis patients .…”
Section: Anti‐inflammatory Neuropeptidesmentioning
confidence: 99%
“…Target sites comprise the cardiorespiratory organs and immune cells [116]. Adrenomedullin has been shown to be anti-inflammatory in animal models of sepsis, pancreatitis, arthritis and colonic inflammation [117][118][119][120].…”
Section: Adrenomedullinmentioning
confidence: 99%
“…Besides its potent vasodilatory and hypotensive effects, adrenomedullin also has an anti-inflammatory effect [ 5 ]. Adrenomedullin can inhibit the production of tumor necrosis factor-α (TNF-α) from activated macrophages [ 6 ] and was found to abrogate inflammation and alleviate systemic bone loss in murine collagen-induced arthritis [ 7 ]. Adrenomedullin may be involved in the pathogenesis of OA through the anti-inflammatory effect.…”
Section: Introductionmentioning
confidence: 99%